Carbon Support Microstructure Impact on High Current Density Transport Resistances in PEMFC Cathode. Issue 6 (2nd April 2020) - Ramaswamy, Nagappan; Gu, Wenbin; Ziegelbauer, Joseph M.; Kumaraguru, Swami
Abstract : Cell voltages at high current densities (HCD) of an operating proton-exchange membrane fuel cell (PEMFC) cathode suffer from losses due to the local-O2 and bulk-H + transport resistances in the catalyst layer. Particularly, the microstructure of high surface area carbon (HSC) support upon which both the platinum catalyst and ionomer are dispersed play a pivotal role in controlling the reactant transport to the active site in the catalyst layer. In this study, we perform a systematic analysis of the underlying microstructure of platinum-cobalt catalyst dispersed on various HSC supports in terms of their surface area and pore-size distribution. The carbon microstructure was found to strongly influence the PtCo nanoparticle dispersion, catalyst layer ionomer distribution and transport losses governing the performance at HCD. Catalyst layer electrochemical diagnostics carried out to quantify local-O2 transport resistance and bulk-H + transport resistance in the cathode were found to be directly correlated to the micropore (<2 nm) and macropore (>8 nm) surface areas of the carbon support, respectively. Finally, a 1D-performance model has been developed to assimilate our understanding of the catalyst layer microstructure and transport resistances at HCD.